Metabolism of styrene by Rhodococcus rhodochrous NCIMB 13259. - Warhurst, A M (1994)
Rhodococcus rhodochrous NCIMB 13259 grows on styrene, toluene, ethylbenzene, and benzene as sole carbon sources. Simultaneous induction tests with cells grown on styrene or toluene showed high rates of oxygen consumption with toluene cis-glycol and 3-methylcatechol, suggesting the involvement of a cis-glycol pathway. 3-Vinylcatechol accumulated when intact cells were incubated with styrene in the presence of 3-fluorocatechol to inhibit catechol dioxygenase activity. Experiments with 18O2 showed that 3-vinylcatechol was produced following a dioxygenase ring attack. Extracts contained a NAD-dependent cis-glycol dehydrogenase, which converted styrene cis-glycol to 3-vinylcatechol. Both catechol 1,2- and 2,3-dioxygenase activities were present, and these were separated from each other and from the activities of cis-glycol dehydrogenase and 2-hydroxymuconic acid semialdehyde hydrolase by ion-exchange chromatography of extracts. 2-Vinylmuconate accumulated in the growth medium when cells were grown on styrene, apparently as a dead-end product, and extracts contained no detectable muconate cycloisomerase activity. 3-Vinylcatechol was cleaved by catechol 2,3-dioxygenase to give a yellow compound, tentatively identified as 2-hydroxy-6-oxoocta-2,4,7-trienoic acid, and the action of 2-hydroxymuconic acid semialdehyde hydrolase on this produced acrylic acid. A compound with the spectral characteristics of 2-hydroxypenta-2,4-dienoate was produced by the action of 2-hydroxymuconic acid semialdehyde hydrolase on the 2,3-cleavage product of 3-methylcatechol. Extracts were able to transform 2-hydroxypenta-2,4-dienoate and 4-hydroxy-2-oxopentanoate into acetaldehyde and pyruvate.(ABSTRACT TRUNCATED AT 250 WORDS)